"How do we use the time?" - an observational study measuring the task time distribution of nurses in psychiatric care - Andreas Glantz; Karin Örmon; Boel Sandström (BMC, 2019)
Abstract Background The nurse's primary task in psychiatric care should be to plan for the patient's care in cooperation with the patient and spend the time needed to build a relationship. Psychiatric care nurses however claim that they lack the necessary time to communicate with patients. To investigate the validity of such claims, this time-motion study aimed at identifying how nurses working at inpatient psychiatric wards distribute their time between a variety of tasks during a working day. Methods During the period of December 2015 and February 2016, a total of 129 h and 23 min of structured observations of 12 nurses were carried out at six inpatient wards at one psychiatric clinic in southern Sweden. Time, frequency of tasks and number of interruptions were recorded and analysed using descriptive statistics. Results Administering drugs or medications accounted for the largest part of the measured time (17.5%) followed by indirect care (16%). Relatively little time was spent on direct care, the third largest category in the study (15.3%), while an unexpectedly high proportion of time (11.3%) was spent on ward related tasks. Nurses were also interrupted in 75% of all medication administering tasks. Conclusions Nurses working in inpatient psychiatric care spend little time in direct contact with the patients and medication administration is interrupted very often. As a result, it is difficult to establish therapeutic relationships with patients. This is an area of concern for both patient safety and nurses' job satisfaction.